Effects of two forms of school-based high-intensity interval training on body fat, blood pressure, and cardiorespiratory fitness in adolescents: randomized control trial with eight-week follow-up—the PEER-HEART study - Domaradzki, Jarosław; Popowczak, Marek; Kochan-Jacheć, Katarzyna; Szkudlarek, Paweł; Murawska-Ciałowicz, Eugenia; Koźlenia, Dawid (Frontiers in Physiology, 2025)
IntroductionThis study examined the effects of 8-week interventions based on two variants of typical exercises, namely, high-intensity interval training (HIIT) and high-intensity plyometric training (HIPT), on body fat (BF%), blood pressure, and cardiorespiratory fitness (CRF). In addition, the sustainability of the effects after another 8 weeks was assessed.MethodsThe project was designed as a randomized controlled trial with eight groups of participants (two variants, two sexes, and two groups (experimental and control)) and was conducted in a school physical education (PE) program. The outcomes analyzed were the BF%, systolic (SBP), diastolic blood pressure (DBP), and CRF expressed in terms of maximum oxygen uptake (VO2max). A total of 307 healthy adolescents participated in this study and were randomly assigned into the two groups. During the 8 weeks, the participants completed two exercise sessions each week with progressively increasing volumes. For the first 2 weeks, the sessions involved four rounds of 20 s of intense effort followed by 10 s of rest; this increased to six rounds during weeks 3–4 and eight rounds during weeks 5–8. The HIPT program was based on plyometric exercises, whereas the HIIT was based on bodyweight resistance exercises.ResultsMultidimensional analysis of variance (ANOVA) indicated a statistically significant second-order interaction (time × variant × group: Ʌ = 0.943, F = 2.20, p < 0.027, η2pG = 0.057, d = 0.25), confirming the changes in the BF%, SBP, DBP, and VO2max dependent on the type of intervention and group assignment. The ANOVA results revealed significant main and interaction effects for BF%, SBP, and DBP, with time and the HIIT variant as the main contributors (BF%: F = 3.911, p = 0.023, η2pG = 0.001, d = 0.04 vs. F = 9.900, p < 0.001, η2pG = 0.001, d = 0.03; SBP: F = 31.801, p < 0.001, η2pG = 0.012, d = 0.16 vs. F = 8.939, p = 0.003, η 2pG = 0.026, d = 0.16; DBP: F = 3.470, p = 0.033, η2pG = 0.002, d = 0.06 vs. F = 4.982, p = 0.026, η2pG = 0.014, d = 0.12). The second-order interaction for VO2max (time × sex × group: F = 6.960, p = 0.001, η2pG = 0.003, d = 0.05) indicated that the improvements over time were not related to the training variant. Although these effects were small (low eta values), post hoc tests (all comparisons in post-intervention, p > 0.05) showed that both the HIIT and HIPT groups exhibited beneficial changes compared to controls; however, no statistically significant differences were observed between the experimental and control groups. Furthermore, the observed improvements were maintained through the 8-week follow-up period, as demonstrated by no significant changes between the post-intervention and follow-up measurements (p > 0.05). Discriminant analysis showed that BF% and SBP were the key variables for the two exercise variants in men, with HIPT yielding greater reductions in SBP and HIIT resulting in more pronounced decreases in BF%.DiscussionIn conclusion, both HIIT and HIPT interventions effectively improved health-related parameters, providing valuable enrichment to the PE lessons in schools. These benefits were also sustained for at least 8 weeks post-intervention.